2009
DOI: 10.1093/ndt/gfp033
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural response of arterialized femoral veins in a rodent AV fistula model

Abstract: Our AVF model in the rat demonstrates maturation effects in fistula veins similar to typical clinical findings in haemodialysis patients. Noninvasive ultrasound proved to be a valuable tool for longitudinal in vivo monitoring of the fistulas in this rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
3
42
0
1
Order By: Relevance
“…51 Finally, as shown in recent studies, in hemodialysis patients undergoing angioplasty of stenotic AVFs, higher plasma levels of ADMA are strongly predictive of the risk for restenosis. 52 The femoral AVF model in the rat, as described in the present and recent studies, 11,14,53 complements other rodent models used to study AVF failure. For example, the murine AVF model recapitulates the salient features of dysfunctional and failing human AVFs, 10 and when created in genetically altered mice, allows the interrogation of the functional significance of specific genes; this murine model was recently used in the examination of the pathobiologic significance of heme oxygenase-1 12 and osteopontin in an AVF, 13 and the therapeutic efficacy of bone morphogenetic protein 7 in this murine model when created in mice with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…51 Finally, as shown in recent studies, in hemodialysis patients undergoing angioplasty of stenotic AVFs, higher plasma levels of ADMA are strongly predictive of the risk for restenosis. 52 The femoral AVF model in the rat, as described in the present and recent studies, 11,14,53 complements other rodent models used to study AVF failure. For example, the murine AVF model recapitulates the salient features of dysfunctional and failing human AVFs, 10 and when created in genetically altered mice, allows the interrogation of the functional significance of specific genes; this murine model was recently used in the examination of the pathobiologic significance of heme oxygenase-1 12 and osteopontin in an AVF, 13 and the therapeutic efficacy of bone morphogenetic protein 7 in this murine model when created in mice with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
“…11,14 These histological findings and the accompanying marked induction of genes incriminated in vascular access dysfunction (for example, MCP-1, IL-6, transforming growth factor-␤1, plasminogen activator inhibitor-1, and matrix metalloproteinase-9), in aggregate, thus demonstrate that this model is a faithful one by which to study the pathophysiologic mechanisms underlying dysfunction of hemodialysis AVFs, and to examine strategies that may extend the longevity of these AVFs. .…”
Section: Discussionmentioning
confidence: 86%
“…Only one death occurred during the procedure, due to uncontrolled bleeding of the artery, and after this case two temporary clips were used together to control the artery. Mortality rates in fistula studies have generally ranged between 0 and 47% [16, 22-24]. Most of the deaths occur 24–48 h after surgery, because of congestive heart failure (CHF) or for unknown reasons [16, 22, 25].…”
Section: Discussionmentioning
confidence: 99%
“…No postoperative deaths and no infections were observed in the current study. Langer et al [24] reported one case of thrombosis after infection in femoral vessel fistulae. The CJF model has some limitations because it is not as simple as the ACF model, using needle piercing and requiring a well-set-up microsurgery research laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The additional advantage of the forearm graft is that it sets the stage for creation of a secondary fistula (25)(26)(27)(28). The upper arm basilic and cephalic veins serve as the effluent conduits for the forearm graft and are subjected to the same mechanical and neuro-humoral signals that are involved in fistula maturation (29). Finally, because these veins have already dilated and their walls are thickened, they can be cannulated for dialysis use after conversion to a secondary fistula with no or minimal delay (27).…”
Section: Suboptimal or Inadequate Forearm Vessels Or Failed Accessmentioning
confidence: 99%